The effect of green lens glasses on intraocular pressure in healthy students experiencing psycho-emotional stress - M. E. Mirgorodskaya; M. N. Mirgorodsky; V. V. Vronskaya; K. V. Tsys; E. S. Kaminskaya (Российский офтальмологический журнал)
Purpose: to evaluate the clinical effectiveness of using green lens glasses to reduce IOP in healthy people during psychoemotional stress. Materials and methods. IOP variation was estimated for 23 students, who alternatively wore green lens glasses for 1 hour and did not wear them. The research was done during classwork so the students experienced intense mental load. Results. With no chromatic optical correction, the average IOP which initially was 15.45 ± 2.37 mm Hg (95% CI: 13.75–17.15), increased after one hour up to 16.85 ± 2.40 mm Hg (95% CI: 15.13–18.57), which was statistically significant (p = 0.029). In the chromatic correction experiment, the initial average IOP was 16.15 ± 2.73 mm Hg (95% CI: 14.87–17.43), and only slightly increased after one hour to reach 16.48 ± 3.0 mm Hg (95% CI: 15.04–17.91), and the change was statistically insignificant (p = 0.526). Side effects of green lens glasses, specifically a change in colour perception, were registered in 96% of the students observed. Conclusion. Green lens glasses reduce the rate of IOP elevation under psychological stress. However, we have not received any information about an IOP decrease achievable by such glasses.